SIGN-R1 contributes to protection against lethal pneumococcal infection in mice - FALLON, PADRAIC (Rockefeller University Press, 2004)
Rapid clearance of pathogens is essential for successful control of pyogenic bacterial infection. Previous experiments have shown that antibody to specific intracellular adhesion molecule-grabbing nonintegrin (SIGN)-R1 inhibits uptake of capsular polysaccharide by marginal zone macrophages, suggesting a role for SIGN-R1 in this process. We now demonstrate that mice lacking SIGN-R1 (a mouse homologue of human dendritic cell?SIGN receptor) are significantly more susceptible to Streptococcus pneumoniae infection and fail to clear S. pneumoniae from the circulation. Marginal zone and peritoneal macrophages show impaired bacterial recognition associated with an inability to bind T-independent type 2 antigens such as dextran. Our work represents the first evidence for a protective in vivo role for a SIGN family molecule.
PUBLISHED
Keywords: DC-SIGN ? marginal zone macrophages ? microbial infection ? innate immunity ? lectin